Granite-related uranium deposits in Argentina: Geological context and new metallogenetic studies. - Álvarez, J. (2020)
In Argentina, Devonian-Carboniferous magmatism has played a very relevant role in uranium metallogenesis, driving magmatic and late-magmatic preconcentration processes, both within and in the periphery of the granitic massifs. This research has characterized different types and subtypes of uranium deposits linked to that fertile magmatism. These new studies on uranium minerals from uranium sites of interest have improved the metallogenetic knowledge of the granite-related uranium deposits, which in turn could aid the exploration for similar uranium deposits. It was determined that granites play an important role both as a uranium source and hosts of diverse types of uranium mineralization. Additionally, it is thought that, at the existing level of knowledge, there are prospects for the discovery and development of new uranium resources related to granites in Argentina.